EKSISTENSI DAN KONTRIBUSI ULAMA PEREMPUAN DI KABUPATEN ACEH BARAT (SUATU ANALISIS PRAKTIK SOSIAL DARI BOURDIEU) - IRMA JURAIDA (Prodi Sosiologi FISIP Universitas Teuku Umar, 2017)
This study discusses about the existence and extent of the contribution of women religious leaders accepted in society in West Aceh district by using sociological analysis (social practice). This study was conducted in Aceh Barat district using a qualitative approach, notably through in-depth interview techniques by way of to-face and observation. According to the thinking of Bourdieu (1990), habitus and domains provide an easy way to see how the process of constructing of the realm of Islamic boarding school and the community and penginternalisasi habitus and religious values, socio-cultural and customs in society that formed the existence of women religious leaders in the community. . the results showed that the existence and contribution of women religious leaders in society, to understand the people of Aceh are still in the capacity of women. Women have not been possible to contribute to the public realm, just in taklim, special lectures for or fellow women and local preachers. Keywords: Existence, contributions, women scholars, Aceh Barat